Calculated carrier mobility of h-BN/γ-InSe/h-BN van der Waals heterostructures. (8th September 2017) - Kang, P; Michaud-Rioux, V; Kong, X-H; Yu, G-H; Guo, H
Abstract: Recent experiments reported excellent transport properties of two-dimensional (2D) van der Waals (vdW) heterostructures made of atomically thin InSe layers encapsulated by two h BN capping layers (ISBN). The carrier mobility of the ISBN films exceeded μ ∼ 1.2 × 10 4 c m 2 V − 1 s − 1 at low temperature, much higher than that of pristine InSe films. It has been puzzling why the relatively inert h BN capping layer could so drastically enhance mobility of the ISBN composite. Using a state-of-the-art first principles method, we have calculated phonon limited carrier mobility of 18 different ISBN films and 6 pristine InSe films with different thicknesses, the largest system containing 2212 atoms. The h BN capping layer significantly alters the elastic stiffness coefficient as compared with pure InSe—thus the acoustic phonons in the ISBN composite—giving rise to the observed large mobility of ISBN films. Of the 18 calculated ISBN films, the ones with no strain at the h BN/InSe interface possess the highest electron mobility, reaching 4340 c m 2 V − 1 s − 1 at room temperature, which could easily go over 10 4 c m 2 V − 1 s − 1 at low temperatures. We conclude that the mechanical properties of the composite 2D vdW ISBN material play the crucial role for inducing the large carrier mobility, a principle that could be applied to many other 2D vdW heterostructures.